Empirical Modeling for Diffusion of Nitrogen into AISI 430 Ferritic Stainless Steel - AUNG NYEIN HAN, AUNG NYEIN (Universiti Teknologi Petronas, 2011)
This study is based on the solution nitriding of ANSI 430 ferritic stainless steel. Solution nitriding play a significant role in enhancing the surface hardness of AISI 430 ferritic stainless steels. However, this particular area need further research in term of empirical modeling for future engineering guidance and references. The study of this project focused on the identification of the appropriate empirical model for diffusion of nitrogen into AISI 430 ferritic stainless steel. And then, the results were compared with the existing experimental results which were conducted on the same temperature. This research starts by searching for any other relevant journal or article published by other researchers and from there, the results were reviewed and useful information were summarized and taken as information to this research. This study involved few analytical calculations, more to theories and literature reviews, research of pre-existing experimental works and results and finally comparison between theoretical results and existing experimental results. As for software, the familiarization of Microsoft Excel is more than enough to solve the developed formulations.